Characterization of Delta Operator for Poisson-Charlier Polynomials - Maheswaran, A. (Journal of Informatics and Mathematical Sciences, 2018)
The aim of the paper is to study the characterization of delta operator associated with some Sheffer polynomials. In this paper, we consider Poisson-Charlier polynomials and investigate the characterization of delta operator via sequential representation of delta operator. From our investigation, we are able to prove an interesting propositions for the above mentioned.